Facile synthesis of GalNAc monomers and block polycations for hepatocyte gene delivery. Issue 28 (29th June 2021) - Bockman, Matthew R.; Dalal, Rishad J.; Kumar, Ramya; Reineke, Theresa M.
Abstract : Here, we present a facile synthetic route for a monomer displaying N -acetyl-d -galactosamine and subsequent copolymerization in a block format with cationic subunits readily accessing liver-targeted polymeric pDNA delivery vehicles with low toxicity. Abstract : The ability to design liver-targeted polymers for nucleic acid delivery vehicles is plagued with difficulties ranging from polymer-mediated cellular toxicity to challenges in synthesizing monomers that enable facile cell-specific polymeric gene delivery vehicles. Herein is presented an improved synthetic route to a N -acetyl-d -galactosamine (GalNAc)-derived monomer (two steps, 91% overall yield) and its incorporation into a library of nine diblock co-polymers with 2-aminoethylmethacrylamide (AEMA) and two end-group functionalized AEMA homopolymers. These polymers were complexed with plasmid DNA (pDNA) into polyplexes and evaluated for the toxicity, uptake and transfection efficiency against cultured hepatocytes (HepG2) at N/P ratios of 2.5, 5, and 10. All polyplexes showed a range of cell survivability between 60–90%, an improvement over JetPEI, a commercial transfection reagent, when dosed at standard concentrations. Although GalNAc block length does not play a significant role in cellular uptake of Cy-5 labeled pDNA, it has a heavy influence on the transfection efficiency of luciferase-encoded pDNA where longer GalNAc block lengths give rise to higher transfection efficiencies. Overall, this work demonstrates a greatly improved route to GalNAc monomer synthesis, which that can be incorporated into polymers that target hepatocytes.